2005
DOI: 10.1002/polb.20577
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental solution and single‐chain properties of polylactides

Abstract: Polylactides (PLA) have been known for several decades and are recently of considerable commercial significance. However, the literature on basic chain properties and solution characterization is divided and inconsistent. In this study, a comprehensive and well‐controlled set of experiments is combined with rigorous quantitative analysis to resolve existing apparent contradictions. Homopolymers and copolymers spanning wide ranges of molecular weight and stereoisomer proportions were prepared by ring‐opening po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 33 publications
6
135
1
Order By: Relevance
“…The standard model for branched polymers was modified to account for the strong steric interactions that occur in bottlebrushes due to the high grafting density of the side chains, as was done previously for similar bottlebrush block polymers (25). Gaussian chains were used to represent the N = N A + N B + N C (LSO) or N = N A + N B + N A′ (LSL′) side chains, and the volumes and unperturbed end-to-end lengths of the side chains were set to known literature values (26,27). For the backbone, a worm-like chain of fixed persistence length was used to handle the strong lateral tension that occurs due to sidechain crowding.…”
Section: Resultsmentioning
confidence: 99%
“…The standard model for branched polymers was modified to account for the strong steric interactions that occur in bottlebrushes due to the high grafting density of the side chains, as was done previously for similar bottlebrush block polymers (25). Gaussian chains were used to represent the N = N A + N B + N C (LSO) or N = N A + N B + N A′ (LSL′) side chains, and the volumes and unperturbed end-to-end lengths of the side chains were set to known literature values (26,27). For the backbone, a worm-like chain of fixed persistence length was used to handle the strong lateral tension that occurs due to sidechain crowding.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10.1 shows the K H values so determined (vertical axis intercepts) to vary over a wide range, from lowest to highest, by a factor of 25! From this analysis [3], it was concluded that the state of the literature regarding Mark-Houwink parameters for PLA was inadequate.…”
Section: Viscometry Of Plamentioning
confidence: 99%
“…Different definitions of the mean squared ''monomer'' step length Because of the confused state of the literature, a careful study [3] was performed to determine appropriate physical constants for PLA under dilute solution conditions. The results of this important study are summarized here with attention focused on the most important results useful for characterizing PLA.…”
Section: Viscometry Of Plamentioning
confidence: 99%
See 1 more Smart Citation
“…For PLA-THF, K =1.74·10 -4 and a = 0.736 [35]. Figure 1 display SEM micrographs of PLA/HT nanocomposites.…”
Section: Viscometrymentioning
confidence: 99%